2006
DOI: 10.1063/1.2219985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of threading dislocation density on Ni∕n-GaN Schottky diode I-V characteristics

Abstract: The impact of threading dislocation density on Ni/ n-GaN Schottky barrier diode characteristics is investigated using forward biased current-voltage-temperature ͑I-V-T͒ and internal photoemission ͑IPE͒ measurements. Nominally, identical metal-organic chemical vapor deposition grown GaN layers were grown on two types of GaN templates on sapphire substrates to controllably vary threading dislocation density ͑TDD͒ from 3 ϫ 10 7 to 7 ϫ 10 8 cm −2 . I-V-T measurements revealed thermionic emission to be the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 42 publications
4
70
2
Order By: Relevance
“…The European Physical Journal Applied Physics [28] I P E GaN 1.0 [29] I P E GaN 1.11 [24] I P E GaN 0.95 ± 0.04 [26] I P E GaN 0.97 ± 0.05 [27] I P E calculated as 1.33 ± 0.1 eV via (4). The same methods and calculations described above yielded Schottky barrier heights of 1.64 ± 0.1 eV and 1.68 ± 0.1 eV for Er:GaN and Yb:GaN, respectively.…”
Section: -P5mentioning
confidence: 99%
See 1 more Smart Citation
“…The European Physical Journal Applied Physics [28] I P E GaN 1.0 [29] I P E GaN 1.11 [24] I P E GaN 0.95 ± 0.04 [26] I P E GaN 0.97 ± 0.05 [27] I P E calculated as 1.33 ± 0.1 eV via (4). The same methods and calculations described above yielded Schottky barrier heights of 1.64 ± 0.1 eV and 1.68 ± 0.1 eV for Er:GaN and Yb:GaN, respectively.…”
Section: -P5mentioning
confidence: 99%
“…Surface alloying can occur [14] and a large range of experimentally measured Schottky barrier heights has been reported (0.76-1.40 eV) at the Au to n-type GaN interface [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], using photoemission spectroscopy (PES), current-voltage (I-V) and capacitance voltage (C-V) characteristics, and internal photoemission [30]. However, the generally accepted value is about 1.08 eV [31].…”
Section: Introductionmentioning
confidence: 99%
“…5(a) and (b), the SBHs were found to be a strong function of temperature and show the unusual behavior of increasing linearly with an increase in temperature from 80 K to 420 K for all of three Schottky contacts. Similar temperature dependent behaviors were reported in an early study for GaN based MS contacts [11,12,[14][15][16][17][18][19]. The ideality factor n is a measure of conformity of the diode to thermionic emission and requires the n to be constant for different temperatures and close to 1 [7].…”
Section: The Modelmentioning
confidence: 56%
“…Several investigations have been reported to analyze the dominant current-transport mechanism in GaN-based Schottky diodes. Tunneling current and thermionic field emission are both considered as dominant current transport mechanisms [8][9][10][11][12][13][14][15][16][17][18][19][20]. Evstropov et al [8,10] and Balyaev et al [13] showed that the current flow in the III-V heterojunctions is generally governed by multistep tunneling with the involvement of dislocations even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation